Conduction mechanism in polymeric membranes based on PEO or PVdF-HFP and containing a piperidinium ionic liquid. (10th March 2019) - Elamin, Khalid; Shojaatalhosseini, Mansoureh; Danyliv, Olesia; Martinelli, Anna; Swenson, Jan
Abstract: Two types of polymer electrolyte membranes were prepared using poly(ethylene oxide) (PEO) and poly(vinylidene difluoride-co-hexafluoropropylene) (PVdF-HFP), with different amounts of the ionic liquid N-methyl-N-propylpiperidinium bis(trifluoromethane-sulfonyl)imide ([PP13 ][TFSI]) added. The results from differential scanning calorimetry and conductivity measurements show that in the case of PVdF-HFP membranes the glass transition temperature Tg decreases and the room temperature ionic conductivity increases with increasing content of the ionic liquid (up to 60 wt.%). However, in the case of PEO based membranes Tg is less significantly affected and the room temperature ionic conductivity increases only up to 30 wt.% of ionic liquid, beyond which a steady value of about 5⋅10 −5  S/cm is reached. The results from Raman spectroscopy show that the characteristic vibrational mode of the TFSI anion at ∼742 cm −1 is weakly affected in the membranes prepared from PVdF-HFP, whereas for those based on PEO it has a clearer composition dependence. These results suggest ion-ion and ion-polymer interactions of different nature, which together with the different nanomorphologies adopted by PEO and PVdF-HFP, as revealed by X-ray scattering, give rise to different composition dependences of the macroscopically measured ionic conductivity.